Phase angle is independently associated with muscle strength across multiple handgrip strength metrics in young adults: A cross-sectional study - Juan Carlos Calderón-González; Luis Hebert Palma-Pulido; Gonzalo Romero-Martínez; Juan Carlos Urriago-Fontal; María Elisa Álvarez-Ossa; Frank Carrera-Gil; Robinson Ramírez-Vélez (PLoS ONE, 2026)
Objective Phase angle derived from bioelectrical impedance analysis has been proposed as a marker of muscle quality associated with muscle function; however, the extent to which its association with muscle strength is influenced by health status, dietary patterns, physical activity, and demographic factors remains incompletely characterized. This study examined the association between phase angle and muscle strength assessed using multiple handgrip strength (HGS) metrics, accounting for relevant clinical and lifestyle factors. Methods This cross-sectional study included 1,125 adults with complete data on phase angle, skeletal muscle mass, and HGS. Phase angle was measured using bioelectrical impedance analysis. Muscle strength was assessed as absolute HGS and HGS normalized to height² (HGS/h²). Low muscle strength was defined using sex- and age-specific international normative values below the 10 th percentile for both HGS and HGS/height². Results Phase angle was consistently associated with muscle strength across both continuous and dichotomous analyses. In multivariable linear regression models, phase angle was positively associated with HGS (β std = 0.26; P < 0.001) or HGS/ h² (β std = 0.38; P < 0.001). In logistic regression models, higher phase angle was associated with lower odds of low muscle strength (in fully adjusted Model 2 HGS: OR, 0.37; 95% CI, 0.29–0.48; HGS/h²: OR, 0.31; 95% CI, 0.24–0.41; both P < 0.001). These associations were independent of sex, age, body fat percentage, physical activity level, and comorbidity categories. Conclusions and relevance Phase angle was consistently associated with muscle strength across continuous and dichotomous outcomes after adjustment for adiposity, physical activity, and comorbidities. These findings suggest that phase angle may have potential utility as a supportive population-level marker in similar young adult populations; however, it should not be used as a substitute for direct muscle strength assessment at the individual level.